Holocene vegetational and climatic history of the Xuguo Co catchment in the central Tibetan Plateau - Shen, Caiming; Liu, Kam-biu; Tang, Lingyu; Peng, Jinlan (Frontiers in Earth Science, 2023)
A 101-cm core was taken from a large lake in the central Tibetan Plateau. Its pollen and loss-on-ignition analyses provide a Holocene vegetational, climatic, and environmental history of the lake catchment. Pollen analysis shows that: dense steppe dominated regional vegetation in the early Holocene (9,200–8,000 cal. yr BP); regional vegetation coverage gradually decreased in the middle Holocene (8,000–4,100 cal. yr BP); and marsh meadow grew on the lake edge and sparse steppe occupied the lake catchment after 4,100 cal. yr BP. Our result also reveals that: 9,200–8,000 cal. yr BP witnessed summer temperature, monsoonal rainfall, and lake-level maxima, as well as few winter and spring aeolian activities and frequent wildfires; 8,000–4,100 cal. yr BP saw a nonlinear decline in temperature, rainfall, lake level, and wildfires; and modern climatic and environmental conditions were established after 4,100 cal. yr BP. Three major monsoon-weakening events at ca. 6,700, 5,800, and 4,100 cal. yr BP were detected by pollen signals and proxies of the climate and environment.